2021
DOI: 10.3389/fneur.2020.609286
|View full text |Cite
|
Sign up to set email alerts
|

Stenting for Symptomatic Intracranial Vertebrobasilar Artery Stenosis in Northeast of China: A Single-Center Study

Abstract: Objective: We described the incidence of surgery-related complications to evaluate the safety of endovascular therapy for severe symptomatic intracranial vertebral basilar artery stenosis (IVBS) in our stroke center in Northeast of China.Methods: Consecutive patients with symptomatic IVBS caused by 70–99% stenosis despite standard medical treatment of antiplatelet agents plus statin were enrolled. Either balloon-mounted stent or balloon predilation plus self-expanding stent was performed. Clinical adverse even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Of the excluded studies, four of the studies 10,[34][35][36] had overlapping patient databases and two of the studies included outcomes that could not be differentiated between the two stent types. 37,38 A total of studies were included, all of them were nonrandomized observational studies.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the excluded studies, four of the studies 10,[34][35][36] had overlapping patient databases and two of the studies included outcomes that could not be differentiated between the two stent types. 37,38 A total of studies were included, all of them were nonrandomized observational studies.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…We also noticed funnel plot asymmetry in all the endpoints ascertained which can be a result of publication or other reporting biases, heterogeneity, and chance. 37,38 We used random effects model to account for heterogeneity and performed subgroup analysis or meta-regression by study design and characteristics as recommended by Metelli and Chaimani. 60 However, due to the small number of studies, our meta-regression was limited since a large ratio of studies to a covariate is required for a meaningful analysis.…”
Section: Limitationsmentioning
confidence: 99%
“…Results showed that BMS could significantly reduce the degree of stenosis compared to SES (Difference in means 5.95, P-value 0/00, and CI 95% −7.27 to −4. 19).…”
Section: Changes In the Degree Of Stenosismentioning
confidence: 99%
“…A higher rate of complications were noted with Mori C lesions compared to Mori A (p = 0.008) and Mori B (p = 0.047). 68,69 Another multi-center prospective registry by Miao et al assessed the safety and efficacy of stenting within 30 days for patients with severe symptomatic stenosis (defined as 70-99%). Among the 159 patients treated with balloon mounted stents, 48 patients had basilar artery stenosis and 48 patients had intracranial vertebral artery stenosis.…”
Section: Clinicalmentioning
confidence: 99%